Development of control system for waste pyrolysis unit of agricultural complex with the application of fuzzy logic - Maksymenko, Andrii (Technology audit and production reserves (Online), 2021)
The object of research is the control system for the pyrolysis reactor of agricultural waste (plant biomass). The subject of research is the stability and the value of the calorific value of synthesis gas formed by pyrolysis of plant biomass. The biggest problem of the technological object (the pyrolysis reactor of agricultural waste) is the high sensitivity of the heating value of synthesis gas to disturbances in the composition of plant biomass. This sensitivity is expressed as a square law of the amount of oxidant required to achieve a high calorific value. Another problem is the deviation of certain time constants of the control object, caused by changes in the chemical composition of the plant biomass. The built control system provides a high calorific value of the generated syngas by determining the composition of the waste, pyrolysis by determining the composition of the generated syngas in a separate isoenthalpic device, and stabilizes it. Information on the composition of raw materials allows to calculate the optimal parameters for the pyrolysis process, and, accordingly, update the controller's task. This information also makes it possible to compensate for changes in the time constants of the control object caused by changes in the chemical composition of raw materials, which made it possible to achieve a high robustness of the system. Compensation for these changes was carried out by training a regression polynomial. The training was carried out on test sets of time constant deviations. The resulting polynomials were used for convolution with membership functions of a fuzzy controller. Such a convolution made it possible to obtain the following membership functions that ensure compliance with the control quality parameters close to those obtained without deviations in the time constants. Simulation of the constructed control system showed a significantly reduced sensitivity of the calorific value to the composition of raw materials, and also revealed a low sensitivity of the control quality from the deviations of the time constants of the control object caused by disturbances in the chemical composition of the waste. The method by which the control system for the pyrolysis reactor was built differs from the existing ones in that the use of information on the composition of the pyrolyzed substance is used to accurately calculate the optimal values of the pyrolysis parameters, as well as to mutate the membership functions of the fuzzy controller. The method can be used in other similar systems designed for the pyrolysis of organic substances in order to expand their scope. In particular, for the integration of such systems into technological objects, they are more sensitive to deviations in the calorific value of the gas used as fuel.